Mixed Matrix Membranes - Casado-Coterillo, Clara (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Mixed matrix membranes (MMMs) have attracted a large amount of interest in research laboratories worldwide in recent decades, motivated by the gap between a growing interest in developing novel mixed matrix membranes by various research groups and the lack of large-scale implementation. This Special Issue contains six publications dealing with the current opportunities and challenges of mixed matrix membranes development and applications to solve environmental and health challenges of the society of 21st century.
English
Keywords: modeling; neural tissue regeneration; membrane fabrication; nanoporous polybenzimidazole membranes; photo-assisted polymerization; poly (?-caprolactone); supported ionic liquid membranes; CH4 selective membranes; flat-sheet membrane; hollow fiber membrane; ion exchange capacity; reduced graphene oxide; polymer of intrinsic microporosity; CH4 solubility; RHO; temperature; porous nanoparticles; protic imidazolium ionic liquids; POSS®; mixed matrix membranes; characterization techniques; membrane modification; in vitro human neural models; small-pore zeolites (CHA; Poly(trimethylsilyl-1-propyne) (PTMSP); LTA); filler dispersion; gas separation; water vapor; gas separation membrane; CO2 separation; nanocomposite membranes; hydrolytic bulk degradation mechanism; PVA; compatibility; borane